Preparation and Electrochemical Characterization of Y-Doped Li1.3Al0.3Ti1.7(PO4)3 Solid Electrolytes for Lithium-Metal Batteries - Zhongran Yao; Fen Qi; Qiang Sun; Lin Ye; Xiaowei Yang; Guojie Chao; Pei Tang; Kongjun Zhu (Crystals)
Lithium-conducting NASICON materials have emerged as a promising alternative to organic liquid electrolytes for high-energy-density Li-metal batteries, owing to their superior ionic conductivity and excellent air stability. However, their practical application is hindered by poor sintering characteristics and high grain boundary resistance. In this investigation, Li1.3Al0.3−xYxTi1.7(PO4)3 (LAYTP-x, x = 0.00, 0.01, 0.03, 0.05, and 0.07) were successfully synthesized via conventional solid-state reaction to explore the impact of Y3+ on both ionic conductivity and chemical stability. The structural, morphological, and transport properties of the samples were comprehensively characterized in order to identify the optimal doping concentration. All samples exhibited a NASICON structure with a uniform distribution of Y elements within the electrolyte. Due to its highest relative density (95.8%), the LAYTP-0.03 electrolyte demonstrated the highest total conductivity of 2.03 × 10−4 S cm−1 with a relatively low activation energy of 0.33 eV, making it suitable for solid-state batteries. When paired with the NCM811 cathode, the Li/LAYTP-0.03/NCM811 cell exhibited outstanding electrochemical performance: a high capacity of 155 mAh/g was achieved at 0.2C after 50 cycles with a Coulombic efficiency of approximately 100%, indicating highly reversible lithium plating/stripping facilitated by the LAYTP-0.03 electrolyte. These results suggest that the LAYTP-0.03 ceramic electrolyte could be a promising alternative for developing safe solid-state Li-metal batteries.